2003
DOI: 10.1136/oem.60.suppl_1.i10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatigue among working people: a comparison of six questionnaires

Abstract: Occup Environ Med 2003;60(Suppl I):i10-i15Aims: To compare the psychometric qualities of six fatigue questionnaires in a sample of working persons. Methods: Internal consistency and test-retest reliability, content validity, convergent validity, and the dimensionality of the fatigue instruments were explored. Results: All scales had a satisfactory internal consistency. Furthermore, based on factor analyses and Mokken scale analyses, all scales were unidimensional and appeared to measure an identical construct.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(151 citation statements)
references
References 40 publications
3
142
2
4
Order By: Relevance
“…16,[37][38][39] In the present study, the items broke down into several specific scales, which only partially supported the hypothesised scales of Although the BDI-FS did not predict outcomes, an inspection of individual items showed that item 1 'Sadness' was predictive of MACE (data not shown).…”
Section: Scaling Resultsmentioning
confidence: 62%
“…16,[37][38][39] In the present study, the items broke down into several specific scales, which only partially supported the hypothesised scales of Although the BDI-FS did not predict outcomes, an inspection of individual items showed that item 1 'Sadness' was predictive of MACE (data not shown).…”
Section: Scaling Resultsmentioning
confidence: 62%
“…A mean score ≥2.2 was considered as high work-related fatigue (31). Overall fatigue represents general mental and physical fatigue (32). It was measured with the 10-item Fatigue Assessment Scale, a valid questionnaire to measure fatigue in the working population (FAS; [32]).…”
Section: Methodsmentioning
confidence: 99%
“…They were eligible to participate if they were currently employed and had high levels of work-related fatigue, as indicated by a high score on two validated questionnaires (ie, ≥2.2 on the emotional exhaustion scale of the Utrecht Burnout Scale [31], and ≥22 on the Fatigue Assessment Scale [32]). Exclusion criteria were (i) ≥1 hour of exercise/week; (ii) fatigue attributable to a medical condition; (iii) currently or in the past six months receiving psychological and/or pharmacological treatment; (iv) drug dependence; and (v) contra-indications to exercise.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…FAS was originally designed to reveal physical and mental fatigue, yet the scale might also be used as a onedimensional questionnaire when a total score of FAS is measured. 17 Each item is scored on a 5-point Likert scale with the total score ranging from 10 to 50. In the present study FAS score was dichotomized and scores ≥ 22 were considered as indication of fatigue.…”
Section: Methodsmentioning
confidence: 99%